Effective Marketing Strategy for ADK Insights - Jennifer Talim (iBuss Management, 2020)
Effective marketing strategy is essential for businesses to be implemented in whatever business stage they are going through right now – to provide sustainable growth and grow market shares. Client acquisition is heavily influenced by the client’s needs and marketing strategy used to portray the best of the company’s offerings. Marketing strategy itself is a larger part that encompasses client acquisition, proving that marketing strategy indirectly influences an agency’s source of longevity. With that in mind, the purpose of this research is to help ADK Insights with their client acquisition problem through creating an effective marketing strategy.With central research question “How can ADK Insights improve its client acquisition through effective marketing strategy in order to increase its sales?”, the research go through various stages – theoretical research on client acquisition, ADK Insights’ current marketing strategy through interviews with ADK Insights’ employees, and analysing consumer insights’ industry best marketing practices through conducting interviews with  both agency-side and client-side professionals. The recommendation given are creating appropriate goal, objective, and targets for ADK Insights, designing positioning strategy, implementing mixture of inbound and outbound marketing, and quarterly assessment. These recommendations are intended to help the agency overcome its struggle in client acquisition to get more sales.Keywords: Client Acquisition, Consumer Insights Agency, Increase Sales, Effective Marketing Strategy